2020
DOI: 10.1002/app.50005
|View full text |Cite
|
Sign up to set email alerts
|

Antistatic packaging based on PTT/PTT‐g‐MA/ABS/MWCNT nanocomposites: Effect of the chemical functionalization of MWCNTs

Abstract: Polymer/carbon nanotube nanocomposites have attracted high interest for a wide spectrum of applications, including antistatic packaging used to protect electronic devices against electrostatic discharge. Polytrimethylene terephthalate (PTT)/maleic-anhydride-grafted PTT (PTT-g-MA)/acrylonitrile butadiene styrene (ABS) blend-based multiwall carbon nanotubes (MWCNTs) nanocomposites were prepared through extrusion. It was conducted chemical functionalization on the MWCNTs by oxidation using nitric acid to introduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 44 publications
(71 reference statements)
0
12
0
Order By: Relevance
“…To sum up, PVC/ASA composites with A-Coal had better antistatic properties than those with the same content of M-Coal. This difference indicated that the A-Coal can be well dispersed throughout the PVC/ASA matrix, mainly attributed to large showing much better [39,40]…”
Section: Antistatic Propertiesmentioning
confidence: 99%
“…To sum up, PVC/ASA composites with A-Coal had better antistatic properties than those with the same content of M-Coal. This difference indicated that the A-Coal can be well dispersed throughout the PVC/ASA matrix, mainly attributed to large showing much better [39,40]…”
Section: Antistatic Propertiesmentioning
confidence: 99%
“…Unlike amorphous polymers, whose free volume of chain tangles is sufficient for the material's barrier property to be ineffective, semi-crystalline polymers, such as PTT, present a greater barrier to water vapor permeation because of the presence of the crystalline phase, which makes the diffusion paths more tortuous, making it difficult for water molecules to pass through the material. [11,42] So, controlling the permeant (gas/vapor/liquid) transport through a polymer is critical in packaging applications. [43] Table 5 shows the WVP results for PTT/PRG and PTT/PTTg-MA/PRG composites.…”
Section: Water Vapor Permeability Testmentioning
confidence: 99%
“…Thus, to obtain antistatic packaging from insulating polymers, an alternative is using antistatic agents as functional fillers that can enhance the polymers' superficial and volumetric electrical conductivity. [6] For example, metallic powders, [7] intrinsically conductor polymers such as polyaniline and polypyrrole, [8] and carbon materials, including carbon black, [9] glassy carbon, [10] carbon nanotubes, [11,12] graphite, and graphene. [13][14][15] In addition, adequate filler content and satisfactory filler dispersion in a polymeric matrix allow conductive paths to form, raise the electrical conductivity and turn common polymers into suitable materials for ESD protection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result may be attributed to the partial destruction of the conductive graphitic structure of CNT caused by the utilization of strong acid in the functionalization. In another work, Braga et al [53] studied the influence of functionalized-CNT on the properties of the PTT/ABS blend. The addition of 0.5 wt% of functionalized-CNT in the polymeric blend decreased the electrical resistivity only by one decade of magnitude when compared with the PTT/ABS blend.…”
Section: Electrical Conductivity Of the Antistatic Agent Particlesmentioning
confidence: 99%